Star-Stuff: a way for the universe to know itself - Desnoyers-Stewart, John (SIGGRAPH '22 Immersive Pavilion, 2022)
Inspired by Carl Sagan, Star-Stuff: a way for the universe to know itself is an immersive experience created to remind immersants of their fundamental connection to humanity and the universe. This hybrid VR artwork brings two people together in a surreal experience that can be shared with a remote stranger or a co-present friend. Their bodies are transformed into constellations surrounded by a myriad of orbiting stars whose lifetimes unfold before their eyes. By reframing the body in a shared aesthetic this unique experience encourages immersants to see themselves and others in a common light, as “star-stuff” brought to life, free of superficial characteristics that divide us.
Keywords: 2-page conference paper; Riecke; Riecke_2022; conferencePapers; john-desnoyers-stewart; proj--star-stuff; project--star-stuff; short conference paper